Breast sarcomas. Literature review - D. A. Ryabchikov; I. K. Vorotnikov; N. V. Chkhikvadze; Ye. Ye. Mironova; M. V. Rodionova; V. A. Mkrtchyan (ABV-press, 2014)
The article presents an overview of the literature about breast sarcomas (nonepithelial malignances). Primary sarcomas are extremely rare, with less than 1 % of all malignant tumors of the breast. Breast carcinomas cause an increased interest of the scientists due to their unique clinical and pathological features and unpredictable prognosis.